Adult type respiratory distress syndrome (ARDS) induced by hydrocarbons. - Luis, J P; Simão, C; Rodrigues, G; Carvalho, A; Almeida, H; Correia, M; Sequeira, J S (Acta Médica Portuguesa, 1996)
The authors present a case of a child aged 32 months, victim of accidental ingestion of an unidentified hydrocarbon product. Sixteen hours following hospitalization, the patient began polypnea with progressive hypoxemia, with the radiograph showing ARDS pattern. Mechanical ventilation was initiated on the 2nd day of admission. During hospitalization the patient developed pneumomediastinum and bilateral pneumothorax which justified active drainage. Inspite of the initial poor prognosis, the patient improved, with no symptoms after discharge. The authors discuss certain theoretical considerations regarding hydrocarbon intoxication.